2013
DOI: 10.1089/jop.2013.0040
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Susceptibility of Staphylococci Isolates from Patients with Chronic Conjunctivitis: Including Associated Factors and Clinical Evaluation

Abstract: Purpose: To determine species of staphylococci in chronic conjunctivitis, their antibiotic susceptibility pattern, patient treatments, clinical course, and clinical conditions. Methods: In this prospective study, 243 conjunctival cultures were taken from 191 patients with chronic conjunctivitis, we obtained staphylococci susceptibility patterns with E-test, and they were analyzed in coagulasepositive and negative. The minimum inhibitory concentration for 90% of isolates (MIC90) was determined for Staphylococcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 17 publications
(16 reference statements)
2
13
1
2
Order By: Relevance
“…Overall, the predominant bacterial isolate was S. aureus (21.5%), as has been reported in Jimma (28.4%) [6], Gondar (21%) [10], Nigeria (23.7%) [23], and India (26.6%) [47]. Staphylococcal isolates were predominant among patients with conjunctivitis, blepharitis and blepharoconjunctivitis diagnoses, similar to that in patients from Jimma [6], Nigeria [23], and Columbia [48]. Conversely,, CoNS isolates were more frequent in keratitis (17%) and endophthalmitis (28.6%) diagnoses, as has been reported in Uganda [49], Mexico [50], Australia [8], Pakistan [51] and India [52].…”
Section: Discussionsupporting
confidence: 68%
“…Overall, the predominant bacterial isolate was S. aureus (21.5%), as has been reported in Jimma (28.4%) [6], Gondar (21%) [10], Nigeria (23.7%) [23], and India (26.6%) [47]. Staphylococcal isolates were predominant among patients with conjunctivitis, blepharitis and blepharoconjunctivitis diagnoses, similar to that in patients from Jimma [6], Nigeria [23], and Columbia [48]. Conversely,, CoNS isolates were more frequent in keratitis (17%) and endophthalmitis (28.6%) diagnoses, as has been reported in Uganda [49], Mexico [50], Australia [8], Pakistan [51] and India [52].…”
Section: Discussionsupporting
confidence: 68%
“…This has been evidenced in post-traumatic infections of Staphylococci , Streptococci , B. cereus and many other gram negative organisms mentioned in this review [ 28 , 68 ]. Bacteria such as P. aeruginosa are resistant to lens cleaning solutions where they adhere and spread through the formation of lipid rafts in contact lens users [ 12 , 69 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the New York Eye and Ear Infirmary, Adebayo and colleagues reviewed 12 years of data from their hospital and found that, among 20,180 conjunctival bacterial cultures, 60.1% were culture-positive and S. aureus was the most common pathogen; in addition, moxifloxacin and gatifloxacin currently appear to be the best choice for empirical broad-spectrum coverage [ 7 ]. Additionally, other reports on the ocular bacterial infection and antibiotic susceptibility have been reported in the literature from various countries, like Colombia [ 8 ], Pakistan [ 9 ], Italy [ 10 ], and Uganda [ 11 ], among other locations.…”
Section: Introductionmentioning
confidence: 99%